Design and implementation of a new multilevel DC -link three-phase T-type inverter / Saddam Shueai Hussein Al-Namer - Saddam Shueai , Hussein Al-Namer (2019)

(untitled)
Multilevel inverters are widely used in industrial applications due to its ability to provide an output signal with low harmonic distortion and superior output voltages. In fact, the low harmonic distortion and high efficiency can be achieved further by increasing the number of voltage levels which might increase the total cost of the systems especially for the complex topologies such as CHB, flying capacitors, and NPC. For a high and medium power application, the voltage stresses across the components are the drawbacks of these inverters. This work proposes (i) a four-level topology for T-type inverters that can be extended to the N-level using unequal voltage sources DC-link, (ii) a new N-multilevel topologies for T-type inverter with reduced number of components in which those topologies constitute the single bridge legs with the shape of the rotated character “T” and (iii) a variable direct current-link circuit, and (iv) a new four-level T-type neutral point piloted (T-NPP) topology with higher efficiency and low THD and with the ability to withstand high voltage stresses, especially for high-power applications. The proposed topologies are designed in such a manner that the dc-voltage stresses split over the components with strong possibilities to increase the load current and switching frequency. Furthermore, the optimized staircase modulation technique is used to generate superior output voltage waveforms. However, the proposed topologies outperform other converters by the high number of output voltage level, low number of components, simple structure and higher efficiency in which four-level T-type inverter reaches to maximum output power 2.250 kW with maximum efficiency equals to 95.38%, conduction and switching losses equal 35.635W, 0.6972 W respectively for each leg. The feasibility of the proposed topologies was validated via theoretical analysis, simulation, and experiments where the prototype was built and used to operate static resistive-inductive (R-L) and dynamic (induction motor) loads.